Design, Implementation, and Evaluation of a Short-Term research Skills Training Course for Clinical Faculty Members: A New Experience at Kerman University of Medical Sciences - Mohammadreza Shakibi; Mina Mobasher; Maryam Okhovati; Elham Iranmanesh; Elham Sharifpoor; Manzume Shamsi Meymandi; Mahmoodreza Dehghani (Kerman University of Medical Sciences, 2020)
Background: Several research skills training courses are designed for both faculty members and students in educational and research institutions around the world. Objevtives: The current study aimed to design, implement, and evaluate a short-term research skills training course for faculty members of Kerman University of Medical Sciences. Methods: The current scholarship study was conducted in three stages, in 2017. The first stage comprised of a comparative study needs assessment, and course design. The training course was conducted with the participation of 30 faculty members and the teaching of 10 experienced professors. Participants were evaluated through practical work and homework. Instructors were evaluated by participants using survey forms. The course was evaluated through interviews with several participants and professors. Results: After eight months of research and holding 16 sessions (which each took between 2 to 4 hours), a course with three main modules was designed in 2017. Instructors used appropriate teaching methods, including interaction with participants, problem-solving, discussing, teamwork, and practicing at home. According to the results of the evaluation, the content of the course was appropriate for the research activities of participants. Besides, they believed that the instructors were among the strengths of the course. Conclusion: Certainly, increasing research skills of faculty members will lead to better guidance of assistants and qualitative improvement of research conducted by students.